PENGARUH JENIS DAN DOSIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill) VARIETAS PERMATA - Maryanto dan Abdul Rahmi (Universitas 17 Agustus 1945 Samarinda, 2015)
Objectives of the research were to study: (1), the effect of different types and dosages of organic fertilizer, (2), to obtain the type and dosage of organic fertilizer suitable for tomato plants.The research was carried out from February 2013 to June 2013. The venue of research held in Kota Bangun III village, Kota Bangun sub district, Kutai Kartanegara Regency. It employed Completely Randomized Design (CRD) with factorial 3x3 and 5 replications. The first factor was organic fertilizer type (K), consisted of 3 sub factors : chicken manure (k1), cow manure (k2) and fertilizer trikoderma (k3). And the second factor was Organic Fertilizer Treatment Dosage (D), consisted of 3 sub factors : d1 = 10 tons of organic fertilizer/ha (50 g per polybag), d2 = dosage of organic fertilizer 20 tons per acre (100 g per polybag), and d3 = 30 tons of organic fertilizer per acre (150 g per polybag).Result of the research indicated that treatment of organic fertilizer type (K) effect very significantly on plant height at 4 weeks and 8 weeks after planting, age of the plant during flowering, number of fruits per plant. But it did no affect significantly on plant height between 2 weeks and 6 weeks after planting. The best results are the heaviest pieces on the type of fertilizer treatment trikoderma (k3) with a weight of 3.75 kg per plant, in reverse, the lightest found in chicken manure treatment (k1), was 3.40 kg per plant.The treatment dosage of organic fertilizer (D) was highly significant on plant height at 4 weeks and 8 weeks after planting, the number of fruits per plant and fruit weight per plant. No significantly effect on plant height between 2 weeks and 6 weeks after planting and the age of the plant during flowering. The best results are the heaviest pieces contained in fertilizer treatment of 30 ton acre (d3) with a weight of 3.64 kg per plant, while the lightest one contained in the fertilizer treatment of 10 tons per acre (k1), was 3.45 kg/ plant.Treatment of interaction (KxD) affected significantly on the number of fruits plant and fruit weight per plant. But it did not affect significantly at the age of 2 weeks, 4 weeks of age, the age of 6 weeks and 8 weeks after planting age and age of the plant during flowering. The best results are the heaviest pieces on the type of fertilizer treatment trikoderma (k3) and 30 tons of organic fertilizer/ha, was 3.88 kg per plant. While the worse results are the lightest pieces of chicken manure treatment type (k1) and dosage of fertilizer 10 tons per acre (d1), was 3.19 kg per plant.